Numerical study on the effects of circuits on thermal-hydraulic performance in an indoor unit with small diameter in air conditioner. (February 2023) - Zhi, Changshuang; Li, Jinbo; Zhao, Fufeng; Li, Rixin; Du, Shunkai; Liu, Yingwen
Abstract: The distributed parameter method is adopted to establish a simulation model of the indoor unit of a split-type household air conditioner with a diameter of 5 mm. The circuits of forward and reverse cross are proposed, and the effects of different circuits on the thermal-hydraulic performance of heat exchanger are revealed. Compared with the prototype, the heat load of the forward and reverse cross is increased more obviously. The forward and reverse cross can realize the strengthening of the heat load by changing the spatial distribution of heat load and temperature difference. The forward and reverse cross under the cooling condition can improve the temperature difference of the second row. The heat loads of the two-phase zone and the vapor phase zone increase to a certain extent. Under the cooling condition for circuit-3, the heat load is increased by 6.65%, and the pressure drop in refrigerant side is slightly increased. Under the heating condition for circuit-3, the heat load and pressure drop in refrigerant side are similar to that of the prototype. Meanwhile, the circuit-3 has the most obvious improvement effect on the non-uniformity of pressure drop under different conditions.